Implementasi Enterprise Resource Planning Modul Purchasing, Sales Dan Inventory Menggunakan Odoo Pada PT. Sukacita Kokoh Bersama - Heni Hermaliani, Eni; Solichatun, Susi; Falla Elmyawan, Nurrasyid; Ilham Arfandi, Muhammad; Oktapiansyah, Yoghi (LPPM Universitas Bina Sarana Informatika, 2023)
PT. Sukacita Kokoh Bersama is a company that focuses on doing supplies and retail business in the field of essential oils and derivatives. Sales operations are recorded using the PHPMyAdmin desktop program and export file reporting using Microsoft Excel which is manually re-edited. This causes frequent over-inventory in some variants with slow sales rates and empty stocks in best-selling products. This research focuses on retail sales data based on existing problems, to help companies design and implement integrated information systems in the form of enterprise resource planning using odoo with operational systems ranging from purchasing, inventory, and sales. Through a system that has been automated and real-time, decision-making in purchasing, warehouses, and sales become more efficient and effective.